The English patient - Ondaatje, Michael, 1943- (London : Bloomsbury, 1992)
'It explores the lives of four people, a young woman and three men, who are stranded in a damaged villa north of Florence as the war retreats around them. In an upstairs room lies the badly burned English patient, alive but unable to move. His extraordinary adventures and turbulent love affair in the North African desert before the War provide the focus around which the vivid tales of his companions revolve'--Jacket.
Keywords: World War, 1939-1945 -- Fiction